Implications of Soil Tillage for Crop and Weed Seeds (Soil Tillage in Agroecosystems, 2002)
In arable fields, soil cultivation is carried out for a number of reasons, and influencing the fate of seeds is one of its most important objectives. It has been evident to farmers for a long time that germination and emergence of seeds can be enhanced by cultivating the soil before sowing. Soil cultivation removes the previous vegetation and hence enhances the competitive situation for the crop. It also facilitates sowing of seeds into the soil. Moisture conditions tend to be more favorable within the soil than on the soil surface. The probability of seeds being removed by birds or other animals is less for seeds that are incorporated into the soil than for seeds that lie on the soil surface.